1993
DOI: 10.1007/bf00634307
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of local sweating in sleep-deprived exercising humans

Abstract: Thermoregulatory sweating [total body (msw,b), chest (msw,c) and thigh (msw,t) sweating], body temperatures [oesophageal (T(oes)) and mean skin temperature (Tsk)] and heart rate were investigated in five sleep-deprived subjects (kept awake for 27 h) while exercising on a cycle (45 min at approximately 50% maximal oxygen consumption) in moderate heat (T(air) and T(wall) at 35 degrees C). The msw,c and msw,t were measured under local thermal clamp (Tsk,l), set at 35.5 degrees C. After sleep deprivation, neither … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…This result for sleep deprivation agreed with decreased M sw,t during exercise in air temperature of 28°C (Sawka et al 1983) but did not agree with increased M sw,t during exercise in air temperature of 35°C (Dewasmes et al 1992). It might be considered that the increase in M sw,t for sleep deprivation was minimized because the air temperature of 30°C in this study, which is lower than skin temperature, was advantageous to dry heat dissipation, besides the role of sleep deprivation in accelerating dry heat dissipation.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This result for sleep deprivation agreed with decreased M sw,t during exercise in air temperature of 28°C (Sawka et al 1983) but did not agree with increased M sw,t during exercise in air temperature of 35°C (Dewasmes et al 1992). It might be considered that the increase in M sw,t for sleep deprivation was minimized because the air temperature of 30°C in this study, which is lower than skin temperature, was advantageous to dry heat dissipation, besides the role of sleep deprivation in accelerating dry heat dissipation.…”
Section: Discussionsupporting
confidence: 66%
“…However, this DT re was the only seasonality of the thermoregulatory response that was found. A higher T sk for sleep deprivation during legbathing in this study was not in agreement with previous descriptions of no change in T sk between sleep deprivation and normal sleep during exercise (Dewasmes et al 1992;Kolka et al 1988;Sawka et al 1983). It was, however, in agreement with Opstad et al (1991), who found a higher T sk for sleep deprivation during exercise.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…In fact, heart rate was actually shown to be reduced after sleep deprivation during sub-maximal exercise (Martin and Haney 1982;Martin and Gaddis 1981). Sleep deprivation has been shown to reduce evaporative cooling and dry heat loss in warm environments (Dewasmes et al 1993;Sawka et al 1984). Endurance performance was however not assessed in these investigations and therefore it is unclear whether the impaired heat dissipation mechanisms reported effect endurance performance.…”
Section: Introductionmentioning
confidence: 96%